1994
DOI: 10.1177/0013164494054001024
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Integrity of Scores from the Fennema-Sherman Mathematics Attitudes Scales: The Attitudes of Public School Teachers

Abstract: The Fennema-Sherman Mathematics Attitude Scales are among the most popular measures used in studies of attitudes toward mathematics. However, the measurement integrity of the scores produced by the measure has not yet been conclusively established. The present study explored this measurement integrity issue by employing data provided by public elementary school teachers of mathematics. Both the measure's factor structure and the measure's sensitivity to social desirability response set were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…Other researchers have also documented the marginal reliability and questionable validity evidence of scores on the available mathematics attitudes instruments (Melancon, Thompson, & Becnel, 1994;Tapia, 2004). One possible reason for existing psychometric problems may be the lack of a robust theory driving the assessment development process.…”
Section: Explanations For Mathematics Deficienciesmentioning
confidence: 99%
“…Other researchers have also documented the marginal reliability and questionable validity evidence of scores on the available mathematics attitudes instruments (Melancon, Thompson, & Becnel, 1994;Tapia, 2004). One possible reason for existing psychometric problems may be the lack of a robust theory driving the assessment development process.…”
Section: Explanations For Mathematics Deficienciesmentioning
confidence: 99%
“…The original FSMAS were developed in 1976 and consist of the following nine subscales: Attitude Toward Success in Mathematics scale; Mathematics as a Male Domain scale; Mother, Father, and Teacher scales; Confidence in Learning Mathematics scale; Mathematics Anxiety scale; Effectance Motivation in Mathematics scale; and Mathematics Usefulness scale. Studies on the psychometric properties of the FSMAS have generally provided support for the reliability and validity of the scales (Melancon, Thompson, & Becnel, ). Additionally, Mulhern and Rae () reported that it is possible to use each subscale separately on its own.…”
Section: Methodsmentioning
confidence: 99%
“…Data from preliminary administrations of the scales were compared to the theoretical framework for each scale and judged for consistency with that framework. Melancon, Thompson, and Becnel (1994) undertook further work to establish the validity of these scales. They investigated the factorial validity using a sample of 174 predominantly female elementary school teachers in an urban public school system.…”
Section: Instrumentationmentioning
confidence: 99%
“…The Fennema-Sherman scales have been the most popular tool for measuring attitudes in mathematics since their development (Melancon et al, 1994;Mulhern & Rae, 1998;Tapia, 2004). They have been used with a variety of age levels from middle school students to adults (Fennema & Sherman, 1977;Fennema & Sherman, 1978;Karp, 1988;Kloosterman, 1988).…”
Section: Instrumentationmentioning
confidence: 99%